Structure of the Cyclic, Cationic Antimicrobial Peptide (KKWWKF) in Octanol Solution: in silico Approach - Seyed Hassan Mortazavi; Mohammad Reza Bozorgmehr; Mohammad Momen Heravi (Indonesian Journal of Chemistry, 2020)
Understanding the mechanism of antimicrobial activity of cyclo-peptides helps to design new drugs based on these compounds. A common aspect of the mechanisms provided for the creation of antimicrobial activity of cyclo-peptides is their interaction with cell membranes. On the other hand, the octanol/water system is a good mimic of the water/membrane interface. Here, the conformational structure of the very short sequences cationic hexapeptide cyclo (Lys-Lys-Trp-Trp-Lys-Phe) has been studied in different concentrations of octanol by molecular dynamics simulation. The concentration of alcohol in the range of experimental concentrations of octanol was considered. The results obtained from calculating the radial distribution function show that the interaction of the peptide with octanol is a mixted of interactions between charged residues with octanol and the interaction of aromatic residues with octanol. These results are in agreement with experimental observations. Also, Lys5 plays a greater role than Lys1 and Lys2 in the interactions with octanol.